Effect of metformin on serum leptin and thyroid stimulating hormone among patients of infertility with polycystic ovary syndrome. - Bhandari,Bijay (2019)
ABSTRACT: Background: Polycystic Ovary Syndrome (PCOS) is the most common cause of anovulatory infertility. Insulin resistance and hyperinsulinemia are important pathophysiologic factors in PCOS associated with an increase in body fat mass. Leptin, an adipocyte secreted hormone is found to be important in energy homeostasis along with reproductive and endocrine physiology. PCOS is associated with increased risk for the spectrum of disorders related to insulin resistance, hyperglycemia, weight gain. Metformin, an insulin-sensitizing drug widely used in type 2 diabetes mellitus to control hyperglycemia and weight gain, is in use nowadays as a treatment option in PCOS women. The objective of this study is to correlate the changes in serum leptin and thyroid-stimulating hormone (TSH) pre-treatment level with three months of post-treatment level among patients of infertility with PCOS. Methods: A cross-sectional study was conducted for one year from July 2018 to June 2019 in the 'infertility out-patient clinic' under the Department of Obstetrics and Gynecology at Tribhuvan University Teaching Hospital. All the patients with the diagnosis of PCOS on basis of Rotterdam Criteria, who met the inclusion criteria during the study period and had given written consent were enrolled, (n=32) in our study. Blood samples were obtained at pre-treatment and after three months of metformin therapy. All data were recorded in a predesigned proforma sheet and descriptive statistical analysis was done by using Statistical Package for Social Sciences (SPSS), version 20. A paired t-test was used to compare the means between the variables and the P-value of <0.05 was considered statistically significant. Result: In the study population (N=32), the mean age (in years) of the patients was Mean ± SD (26.56 ± 2.62). Mean body weight (in kg) of the study population was Mean ± SD (58.75 ±5.41). The mean BMI was Mean ± SD (24.79 ± 2.46. The mean period (in months) the couples were trying to conceive for was Mean ± SD (28.16 ± 12.72). In this study, after three months of metformin therapy, there was a decrease in BMI (Mean 24.79 to 24.56), serum leptin (Mean 13.92 to 10.75) and serum TSH (Mean 3.67 to 3.00) in comparisons with pre metformin treatment value. Moreover, the mean serum leptin level decreased significantly (P=0.006) (95% CI of 0.99-5.36). Similarly, the decrease in TSH and BMI was also statistically significant(P=0.010) (95%CI .17 to 1.16) and (P=0.004) (95% CI of 0.08-0.39). However, the correlation between serum leptin and serum TSH level was not significant. Conclusion: Metformin results in a decrease in body mass index, serum leptin and serum TSH level among infertility patients with PCOS. Keywords Infertility, PCOS, Metformin, Leptin, Thyroid Stimulating Hormone